Efeitos da psicoterapia analítica funcional sobre mudanças comportamentais nos contextos clínico e natural - Santos, Weslem Martins (2022)
This dissertation aimed to evaluate the effects of Functional Analytic Psychotherapy (FAP) on behavioral changes in clinical and natural contexts. To meet this objective, three studies that reviewed FAP research were made. Only single-subject research was analyzed, a behavior investigation methodology aligned with the assumptions of radical behaviorism, the philosophy on which FAP is based upon. The first study evaluated the methodology of single-subject research (from 1990 to 2020) that sought to investigate the effects of the clinical application of FAP. As it was a methodological review, it offered indications about the epistemological quality of FAP single-subject research, but did not provide an analysis of the results obtained in them. In this scenario, the second study (from 1990 to 2021) aimed to expand the research sample of the first, including other types of research reports and databases, keeping the examination of methodological quality and analyzing the results of the application of FAP on behavioral changes in the clinical and natural contexts, identifying critical variables that could affect them. Finally, because change in the natural context must be the ultimate goal of every behavioral intervention, the third study examined how in FAP single-subject research (from 1990 to 2021) the generalization of behavioral repertoires trained in the clinical context has been promoted and evaluated. According to the results, there is empirical evidence that the application of FAP promotes behavioral change in the clinical context, but only preliminary data that such change generalizes to the natural context. It was noticed that few studies promoted and directly evaluated the generalization in FAP, and the results obtained were varied. Limits of research designs are discussed and methodological guidelines for future investigation of FAP are provided